Annual Address to the Board of Governors, September 25, 1967 - Woods, George D. (World Bank, Washington, DC, 2020)
George D. Woods, President of the World Bank Group, spoke about the following: the record of the World Bank Group's activities of the past fiscal year; finance for the International Development Association (IDA); education, teaching new skills, and cultivating new attitudes toward social and economic change; exports of the less developed countries; and the effectiveness of development finance.